Molecular Biotechnology - Sedykh, Sergey (IntechOpen, 2021)
Biotechnology is a unit of engineering biology that studies ways of using living organisms, their systems, or metabolic products to solve technological problems. This book describes the modern trends and progress in biocatalysis and biotechnology, highlighting the versatility of both technologies in science and industry today. Chapters cover such topics as biocatalytic methods for solving problems of processing renewable raw materials, hydrolase-catalyzed reactions in organic synthesis, the use of biocatalytic technologies in pharmaceuticals, electrochemical techniques for the detection of breast cancer biomarkers, the oxidation and photocatalytic treatment of textile wastewater, and chitin hydrolysis.